IMPROVEMENT OF THE MECHANISM OF FINANCIAL SUPPORT SMALL INNOVATIVE ENTERPRISES BASED ON UNIVERSITIES - Romanovich, Liudmila; Anatolievich Doroshenko, Yuri; Vladimirovna Somina, Irina; Alekseevna Romanovich, Marina; Nikolayevna Ryapukhina, Viktoriya (Journal of Applied Engineering Science, 2015)
The Russia, like the advanced foreign countries, and develops innovative ways. In the article the questions of improvement of the mechanism of financial support of small enterprises, organized on the basis of universities. The authors analyzed the positive international and Russian experience in this field and recommendations are given based on the results of implementation of certain provisions of the Belgorod State Technological University named after V. G. Shukhov (Russia, Belgorod).